APLIKASI TEKNOLOGI PLTMH TURBIN PROPELLER OPEN FLUME SEBAGAI PEMBANGKIT LISTRIK DESA - Aris Suryadi; Mochamad Faisal; Berayan Munthe; Mindit Eriyadi; Junaidy Burhan (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
Berecek Village, located in Sukatani District, Purwakarta Regency, West Java Province, has a river that has not been used optimally. This community service aims to utilize the available water energy so that it can produce Micro Hydro power plants. The manufacture of a micro-hydro power plant starts from measuring water potential, designing turbines and generators, then observing the work system and estimating the electrical power that will be generated. From the survey results, it is known that the water discharge is 0.0059 m3 / s and has a fall height of 4 m. This data is used to select the type of turbine, reservoir selection, quick pipe, and generator design. The results of the manufacture of micro power plants obtained by designing using an open flume propeller turbine with a turbine rotation speed of 2063 rpm, this PLTMH is able to produce turbine power of 1346 watts with a water discharge of 45 liters / second so that the power obtained is 1076 watts.Â